Web-based Faculty Development Management System (American Journal of Geospatial Technology, 2023)
As the world kicks back from the aftermath of the COVID-19 pandemic, educational institutions have thus embraced the significant contribution of digitization in their day-to-day operations. As a university, Cebu Technological University Tuburan Campus had also implemented hybrid transactions, providing digital measures to most of its processes including delivery of instructions, students information systems as well as biometric daily time record. This project was developed to provide a database for faculty profile which is responsive to the professional growth of faculty members in order to provide ready reference where needed like organizational changes, among others. The system was built using PHP, HTML, CSS, Bootstrap, JavaScript, and MySQL. Upon testing, the web-based faculty development management system was able to accept faculty registration, handle profile enhancement by individual faculty users as well as output reports according to pre-specified keyword such as subjects handled, designations, academic rank and educational background. Further improvements of the system were also noted like research expertise matching for the purposes of peer reviews and references for consultancy and expert opinions.